HUBUNGAN KINERJA DAN MANFAAT KOPERASI PERTANIAN DI KABUPATEN KOLAKA - Ilma Sarimutaqiyma Rianse; Slamet Hartono; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This research aimed at investigating : (1) the analysis of cooperation based on agricultural criterion in Kolaka District based on cooperation performance analysis based on agricultural criterion in Kolaka District according to cooperative development orientation and cooperation classification orientation; (2) the cooperation performance based on farmer’s perception and cooperation apparatus; (3) find out the benefit found by the farmer as the member; (4) the analysis of correlation between performance and benefit obtained by farmer as cooperation member. This research applied analytical method. The data used consists of primary and secondary data. Primary data in this research is taken from questioner answer returned by cooperation apparatus respondent and stakeholders who asses the performance and benefit from 10 Agriculture Cooperation of Kolaka District. Secondary data obtained were as: (a) the data of financial report or the balance 10 Agriculture Cooperation in Kolaka District year 2006-2010, (b) the data of profit and loss data 10 Agriculture Cooperation in Kolaka District year 2006-2010. The research finding shown that based on Cooperation Cllasification Orientation, the Agriculture Cooperation in Kolaka District in average was 61.58 in 2007 and included quite good category. In 2008, the average of the cooperation performance was 62.05 and included in quite good category. In 2009 the average of cooperation performance was 62.38 and included in quite good category. In 2010 the average of cooperation performance was 61.28 and include in quite good category. Then, majority of cooperation apparatus and stakeholders asses that agriculture cooperation in Kolaka District include in quite good criteria that is 48.75%. furthermore, majority of respondents asses that agriculture cooperation in Kolaka District is beneficial, that is 65%. Based on SEM analysis, the correlation of agriculture cooperation performance positively correlates with the finding benefit by farmers. The correlation of coefficient value of 0.85 has statistical value 14.40. the correlation of standardization value of 0.85 shows the performance and beneficial agriculture cooperation which brings the real correlation. Sequentially, the performance components give the biggest to smallest con tribution that is, caring towards the community is 0.86. the component of voluntary and opened membership is 0.80. the controlling by member democratically is 0.79. the economically participant of the member is 0.71. the education and training give contribution to 0.25. then to components of cooperation benefit sequentially give the biggest to smallest contribution that is marketing economy benefit is 0.96. credit benefit is 0.88. economical benefit of farmer necessity is 0.86. the contribution to social benefit is 0.48.